Comparison of simple discectomy and uninstrumented lumbar interbody fusion in patients with lumbar disc herniation (Annals of Medical Research, 2021)
Aim: This study aimed to compare the surgical outcomes of simple discectomy (SD) and uninstrumented posterior lumbar interbody fusion (PLIF) or transforaminal lumbar interbody fusion (TLIF) in patients with lumbar disc herniation (LDH). Materials and Methods: The files of randomly selected 100 patients with LDH, who underwent SD, were analyzed. The patients were divided into two groups as Group 1 involving 50 patients undergoing SD alone and Group 2 involving 50 patients undergoing SD plus unilateral PLIF and TLIF without posterior lumbar instrumentation. The pain was measured by the visual analog scale (VAS) and the functionality of the patients was measured by the Oswestry disability index (ODI).Results: In both groups, leg and low back pain VAS scores and ODI scores improved significantly one year after surgery (p0.001). There was a significant increase in the VAS scores of Group 2 in the first month compared to Group 1 (p0.05). Conclusion: This study has shown that PLIF and TLIF performed following unilateral SD without posterior lumbar instrumentation support in single-distance LDH treatment will not be sufficient.
Keywords: Back pain; discectomy; interbody fusion; lumbar disc herniation